Revealing tattoo traditions in ancient Nubia through multispectral imaging - Anne Austin; Brenda J. Baker; Tatijana M. Jovanović (Proceedings of the National Academy of Sciences, 2025)
Evidence for tattooing in ancient Nubia is long-standing, although no systematic studies have compared application techniques, motifs, and the demography of tattooed individuals. We surveyed 1,048 Meroitic to medieval (c. 350 BCE–1400 CE) human remains from Semna South (n = 589), Kulubnarti (n = 406), and the Qinifab School site (n = 53). We recorded where skin preservation was sufficient for tattoo observation and used multispectral imaging methods to identify motifs and application techniques. We documented tattooing in 27 individuals of both sexes, ranging from infants to older adults. A shift in both motifs and methods used is apparent in the medieval Christian period. With at least 19% of Kulubnarti individuals displaying tattoos, this investigation demonstrates the importance of systematic surveys to detect tattooing and illuminate varying practices over time.